2019
DOI: 10.5588/ijtld.18.0378
|View full text |Cite
|
Sign up to set email alerts
|

Provider barriers to the uptake of isoniazid preventive therapy among people living with HIV in Ethiopia

Abstract: SETTING: Sixty-seven government health facilities providing tuberculosis (TB) and human immunodeficiency virus (HIV) services across Ethiopia. OBJECTIVE:To examine clinician barriers to implementing isoniazid preventive therapy (IPT) among people living with HIV. DESIGN:A cross-sectional study to evaluate the provider-related factors associated with high IPT coverage at the facility level. RESULTS:On bivariate analysis, the odds of high IPT implementation were lower when clinicians felt patients were negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Finally, our study results also show that the 4 year survival of PLHIV on ART and IPT was better than those who were not initiated on IPT. This is in line with other studies from Africa that have shown that provision of IPT along with ART not only prevents TB, but also has other survival benefits depending upon the community settings in which IPT services are implemented [9, 10, 19, 30, 32]. We could not investigate whether this is due to increased protection against TB disease or due to some other pathway in our study due to the small sample size (zero events in the IPT initiated group).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, our study results also show that the 4 year survival of PLHIV on ART and IPT was better than those who were not initiated on IPT. This is in line with other studies from Africa that have shown that provision of IPT along with ART not only prevents TB, but also has other survival benefits depending upon the community settings in which IPT services are implemented [9, 10, 19, 30, 32]. We could not investigate whether this is due to increased protection against TB disease or due to some other pathway in our study due to the small sample size (zero events in the IPT initiated group).…”
Section: Discussionsupporting
confidence: 90%
“…Countries were disproportionally represented. The majority of studies were conducted in South Africa (n = 11) [37, 42, 47, 50-52, 54, 63-65, 67], Uganda (n = 9) [31-33, 38-40, 44, 56, 66], Tanzania (n = 5) [15,35,36,47,60], Kenya (n = 4) [45,47,49,68], Zimbabwe (n = 3) [33,34,47], Ethiopia (n = 3) [47,53,58], and Nigeria (n = 3) [43,47,57]. Another fifteen countries were represented in only one or two studies.…”
Section: Description Of Studies Included In the Systematic Reviewmentioning
confidence: 99%
“…Some studies were conducted in multiple contexts. Patients (n = 24) [31, 32, 35, 36, 38, 43, 44, 46, 48-52, 54, 55, 58-66], health providers (n = 14) [14,15,36,38,39,45,46,51,53,54,62,63,67,68], and health facilities (n = 14) [15, 33, 36, 37, 39-42, 44, 45, 49, 56, 57, 67] were the study subjects of interest most frequently represented in this review, with at least one of the three study groups included in thirty-eight studies (95%). Few studies included other study subjects, explicitly caregivers [15,34], community members [38], other stakeholders [14,45,46,56], districts [38], and countries [47].…”
Section: Description Of Studies Included In the Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations